XForms : XML Powered Web Forms - Raman, T. V. (Addison-Wesley Professional, 2003)
Praise for XForms: XML Powered Web Forms "XForms is an exciting new technology for designing Web forms in an elegant and accessible way. Raman's book provides strong motivations for flexibility in the design of human-machine interactions, and explains how to use XForms to this end in crystal-clear prose."--Eve Maler XML Standards Architect, Sun Microsystems "Interactive forms technology is the logical evolution of Web user interface design. XForms represents a significant leap forward in that evolution." - Sean McGrath CTO, Propylon "The greatest strength of this book is the skill with which T.V. Raman links the XForms technology with the larger context of the Web. The limitations of HTML forms, the ways in which XForms provides a better foundation for Web and Web service user interfaces, and the opportunities for an XForms-powered Web that is accessible to all users and devices are outlined and brought together in a compelling way." - Michael Champion Advisory Research and Development Specialist, Software AG "Raman's book gives the reader an excellent explanation of the emerging W3C XForms recommendation. It's a well-organized and well-written book that begins with a gentle introduction to the concepts that motivated the development of XForms and then provides a reasonable overview of the relevant XML technology related to XForms. Most of the book covers XForms components: user interface controls, model properties, functions, actions, and events. It concludes with XForms as a Web service, offering multi-modal access and accessibility. In light of the October 2003 deadline for U.S. federal agencies to comply with the mandate of the Government Paperwork Elimination Act (GPEA) to give citizens the opportunity to provide information online, this important technical work comes none too soon. As T.V. masterfully elucidates, XForms provides the 'last mile' in 'connecting users to their data.' Insightfully, he also observes 'the document is the human interface' to data-an understanding without which the challenge to make eGov services 'citizen-centered' simply cannot and will not be met." - Owen Ambur Cofounder and Cochair, XML Working Group, U.S. CIO Council "I found the author's straightforward style quite comfortable and informative. I heartily recommend this book, especially for government XML developers interested in the broader area of E-Forms. Understanding XForms is key to developing robust and flexible E-Forms solutions that separate cont ...